Angular distributions of the alpha particle production in the 7Li+144Sm system at near-barrier energies - Carnelli, Patricio Francisco Florencio (2015)
We have studied the production of alpha particles in reactions induced by 7Li projectiles on a 144Sm target at bombarding energies of 18, 24 and 30 MeV over the 15°-140° angular range. The purpose of the investigation has been to determine the contribution of different mechanisms in reactions that involve weakly bound projectiles. We have included in our analysis several processes that can either directly or sequentially lead to the emission of alpha particles: complete fusion, direct transfer of 3H, capture breakup (incomplete fusion, sequential complete fusion) and non-capture breakup. In order to distinguish alpha particles stemming from these processes it is necessary to determine the mass and charge of the reaction products and to obtain precise measurements of their energies and scattering angles over relatively wide ranges of these variables. We have done this using a detection system consisting of an ionization chamber plus three position sensitive detectors. We present results of these measurements and a preliminary interpretation based on kinematical considerations and comparisons with predictions from a statistical model.